A cryptic EWSR1:DDIT3 fusion in myxoid liposarcoma: Potential pitfalls with FISH and cytogenetics. Issue 3 (24th November 2022) - Ibstedt, Sebastian; de Mattos, Camila Bedeschi Rego; Köster, Jan; Mertens, Fredrik
Abstract: Myxoid liposarcoma (MLS) is molecularly characterized by fusions involving the DDIT3 gene in chromosome band 12q13; the fusion partner is FUS in band 16p11 in 90–95% of the cases and EWSR1 in band 22q12 in the remaining 5–10%. Hence, molecular studies, often fluorescence in situ hybridization (FISH) for DDIT3 rearrangement, are useful for establishing a correct diagnosis. Although all MLS tumors should have DDIT3 fusions, it is important to be aware of reasons for potential false‐negative results. We here present a case of MLS that was negative for FISH for DDIT3, that showed an unexpected t(11;22) at G‐banding, but that displayed a characteristic EWSR1 :: DDIT3 fusion at RNA‐sequencing. The results suggest that neoplasia‐associated fusions that, due to the transcriptional orientations of the two genes involved, cannot arise through only two double‐strand breaks are more likely to be associated with negative FISH‐findings and unexpected karyotypes.